Comparative Analysis of Black-Box and White-Box Machine Learning Model in Explainable Phishing Detection - Abdullah Fajar; Setiadi Yazid; Indra Budi (Universitas Suryakancana Cianjur, 2026)
Explainability in phishing detection model can support a further solution of phishing attack mitigation by increasing trust and understanding how phishing can be detected. The aims of this study to determine and best recommendation to apply an approach which has several components with abilities to fulfil the critical needs A methodology starting with analyzing both black-box and white-box models to get the pros and cons specifically in phishing detection. The conclusion of the analysis will be validated by experiment using a set of well-known algorithms and public phishing datasets. Experimental metrics covers 3 measurements such as predictive accuracy and explainability metrics. Both models are comparable in terms of interpretability and consistency, with room for improvement in diverse datasets. EBM as an example of white-box model is generally better suited for applications requiring explainability and actionable insights. Finally, each model, white-box and black-box model has positive and negative aspects both for performance metric and for explainable metric. It is important to consider the objective of model usage.